The influence of beauty influencers' expertise on Chinese consumers' intention to purchase beauty brands - Wang, Zhaobo (2022)
Abstract As social media continues to advance, consumers increasingly rely on social media to access information about beauty products, which has led to a proliferation of beauty influencers. Beauty influencers have become an important source of information on beauty products for many consumers by posting information and tips about beauty products on social media platforms to showcase their expertise. The content shared by beauty influencers on social media platforms is also subliminally influencing consumers' attitudes, perceptions and behaviours. The impact of social media influencers as a marketing communication tool has been extensively studied. Different scholars often use expertise as an important feature of source credibility models to measure the credibility of celebrities and social media influencers. However, most scholarship on this expertise feature has been measured on a single dimension. However, the degree of expertise of influencers in specialist domains should be measured more comprehensively. Therefore, this study draws on research from other fields to categorise expertise into two dimensions, domain depth and domain breadth, for research. This dissertation chooses to examine the expertise of beauty influencers and explore their influence on consumers' intention to purchase beauty brands along two new dimensions, domain depth and domain breadth, respectively. In addition, this study will investigate whether influencer type has a moderating role in the relationship between beauty influencers' expertise (domain depth and domain breadth) and consumers' intention to purchase beauty brands. This study focuses on Chinese consumers who are aware of or have followed any influencers on Chinese social media platforms and uses a quantitative research methodology to collect a total of 184 online questionnaires to explore the impact of beauty influencers' expertise on Chinese consumers' intention to purchase beauty brands. In addition, the study used established scales from existing research to measure the dimensions of expertise and purchase intention and used SPSS software to process the questionnaire data to test the research model and hypotheses presented in this study. The results of this study show that the domain depth of beauty influencers has a significant effect on Chinese consumers' intention to purchase beauty brands; the domain breadth of beauty influencers does not have a significant effect on Chinese consumers' intention to purchase beauty brands; the type of influencer does not moderate the relationship between the domain depth of beauty influencers and Chinese consumers' intention to purchase beauty brands, but the type of influencer does not moderate the relationship between the domain breadth of beauty influencers and Chinese consumers' intention to purchase beauty brands. Still, the type of influencer does not moderate the relationship between the domain breadth of beauty influencers. However, influencer type has a moderating effect on the relationship between the domain breadth of beauty influencers and Chinese consumers' intention to purchase beauty brands. Marketers of beauty and fashion brands can use the results to select more appropriate social media influencers for their marketing campaigns. This dissertation also concludes with some suggestions for future research.